Differential expression of HSP70 and ultrastructure of heart and liver tissues of rats treated with adriamycin: protective role of L-carnitine. - Strauss, Mirian; Porras, Noraidys (Investigación Clínica, 2009)
The anticancer drug adriamycin has been associated to tissular oxidative stress. In this regard, the promotion of anti-stress protein synthesis by L-carnitine has been suggested in rat adriamycin-induced cardiomyopathy in the long-term. However, the citoprotective role of L-carnitine in cardiac and hepatic tissues after short-term adriamycin treatment is unknown. HSP70 in the supernatant of the homogenized cardiac and hepatic tissues after short-term adriamycin treatment was determined by Western blot analysis with and without L-carnitine protection and compared to the subcellular characteristics of both tissues by transmission electron microscopic analysis. Female Sprague-Dawley rats (n = 6), body weight 40-60g, were randomized into four groups: control, adriamycin, L-carnitine and L-carnitine-adriamycin. Saline, adriamycin (15 mg/kg body weight) and L-carnitine (20 mg before adriamycin) were given intravenously (0.1 mL). HSP70 accumulation was different between the control and the adriamycin samples of both tissues. HSP70 was higher in the liver than in the heart both with and without L-carnitine protection. The nuclei of heart cells, in the adriamycin group showed alterations including, form and irregular perinuclear cysternae with invaginations of different sizes that were not observed in the L-carnitine”“adriamycin samples. Considering the differential expression of HSP70 between liver and heart, our results may be important for understanding the role of these proteins in the adriamycin-induced distinct levels of organ damage and dysfunction. We suggest that L-carnitine exogenous administration might enhance the relationship between the cellular energy state and the activation of heat shock response by an unknown mechanism. L-carnitine may enhance HSP70 in a cellular-type manner.